Population characteristics and impacts on woody vegetation of elephants on Nazinga Game Ranch, Burkina Faso - Theophane Damiba; Ernest Ables (Pachyderm)
A total count identified 268 elephants while a transect sample survey estimated 234-379 animals in Nazinga Game Ranch. A total count seems to be the most acceptable method of monitoring the population. The Nazinga population is young with 79% under 15 years and a sex ratio favouring females. Since the ranch population is well protected, it is expected to increase rapidly, and significant effects on both vegetation and land use conflict with surrounding human settlement are foreseen.